Pengaruh Konsentrasi Nutrisi AB Mix Terhadap Pertumbuhan dan Hasil Sawi Hijau (Brassica juncea L.)dengan Hidroponik Sistem Rakit Apung - Arjuna Kesuma; Fetmi Silvina; Isna Rahma Dini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2022)
Green mustard is a vegetable plant that is generally cultivated in highland areas, but mustard greens can also be grown in lowland areas. The many benefits of mustard greens, it is necessary to make efforts to increase the yield by paying attention to the way of cultivation, such as hydroponic cultivation. Hydroponic cultivation is one solution to meet the needs of vegetables in urban areas because it can be grown on limited land. The advantages of hydroponic cultivation include higher production, compared to conventional planting. The nutrients provided in hydroponic cultivation are AB Mix nutrient solutions, where this nutrient solution contains macro and micro nutrients needed to support plant growth and production. This study was a completely randomized design trial (CRD) consisting of 5 treatments and 4 replications. The treatments in this study were AB Mix 6 ml.l-1, AB Mix 9 ml.l-1, AB Mix 12 ml.l-1, AB Mix 15 ml.l-1, and AB Mix 18 ml.l- 1. Parameters observed were plant height, number of leaves, leaf length and width, plant fresh weight, edible fresh weight, and root volume. The results of the study were statistically analyzed by Duncan's multiple-distance test at 5% level. The results showed that giving AB Mix 9 ml.l-1 was the best treatment which gave results that were not significantly different from other treatments. Based on the results of the study, it can be seen that the combination treatment of high AB Mix nutrients does not necessarily increase the growth of mustard greens hydroponically well. Keywords: sawi hijau, AB mix, hidroponik rakit apung